2009
DOI: 10.1016/j.jfms.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for feline immunodeficiency virus antibody test status in Cats Protection adoption centres (2004)

Abstract: A study was carried out to determine the prevalence of feline immunodeficiency virus (FIV) within a population of cats entering 10 UK adoption centres run by Cats Protection. All cats entering the adoption centres during 2004 were tested for FIV using a rapid enzyme immunoassay antibody test. The overall prevalence of positive test results was 3.1% (95% confidence intervals (CI) 2.7-3.5%), whilst the prevalence at different adoption centres varied from 0.8% (95% CI 0.1-1.5%) to 6.7% (95% CI 4.9-8.5%). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Several previous studies have reported male sex, older age and free‐roaming lifestyle as being significantly associated with the risk of FIV seropositivity (Levy and others 2006, Norris and others 2007, Macieira and others 2008, Blanco and others 2009, Gleich and others 2009, Murray and others 2009). The present study failed to demonstrate any of these risk factors in this group of cats.…”
Section: Discussionmentioning
confidence: 94%
“…Several previous studies have reported male sex, older age and free‐roaming lifestyle as being significantly associated with the risk of FIV seropositivity (Levy and others 2006, Norris and others 2007, Macieira and others 2008, Blanco and others 2009, Gleich and others 2009, Murray and others 2009). The present study failed to demonstrate any of these risk factors in this group of cats.…”
Section: Discussionmentioning
confidence: 94%
“…Taking into account the sensitivity and specificity of the test used (Hartmann and others 2007), the estimated true prevalence for FIV was 19.3%; however with wide 95% CI (14.7% to 24.0%), which reduces slightly the reliability of this estimation. This FIV seroprevalence is much higher than most of those previously reported from European countries, including northern Belgium, whatever the lifestyle or health status of the population studied (Hosie and others 1989, Lutz and others 1990, Hartmann and Hinze 1991, Arjona and others 1992, Bandecchi and others 1992, Ueland and Lutz 1992, Fuchs and others 1994, Peri and others 1994, Sukura and others 1992, Holznagel and others 1997, Knotek and others 1999, Dorny and others 2002, Muirden 2002, Bandecchi and others 2006, Gleich and others 2009, Murray and others 2009, Duarte and others 2012, Spada and others 2012, Rypuła and others 2014). In addition, the mean FIV seroprevalence over three years in the present study is likely an underestimation of the actual prevalence, since FIV‐positive cats were systematically removed from the population since 2010, which introduced a bias in the estimation of crude FIV seroprevalence during the years 2011 and 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The overall FeLV seroprevalence was reported to decrease over time, likely in correlation with the widespread use of vaccination and test and removal programmes at breeding colonies (Gleich and others 2009). In some studies, the risk factors for FIV and/or FeLV infection were assessed (Bandecchi and others 2006, Levy and others 2006, Murray and others 2009, Bande and others 2012, Spada and others 2012). Factors such as age, sex, behaviour, lifestyle/type of habitat and health status have been shown to be associated with risks of FIV, and sometimes FeLV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Their prevalence differs according to geographic regions and indoor/outdoor status Norris et al, 2007). Common risk factors are geriatric cats, male gender, mixed breeding, aggressive behavior, co-infection with other retroviruses and outdoor contact with non-hierarchical cat communities (Murray et al, 2009). Even with more sensitive diagnostic tests and a good therapeutic approach, retroviruses remain a problem among animal rescue shelters Lutz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%